Biomechanical analysis of the cephalomedullary nail versus the trochanteric stabilizing plate for unstable intertrochanteric femur fractures. (December 2016) - Walmsley, David; Nicayenzi, Bruce; Kuzyk, Paul RT; Machin, Alan; Bougherara, Habiba; Schemitsch, Emil H; Zdero, Radovan
Unstable intertrochanteric fractures are commonly treated with a cephalomedullary nail due to high failure rates with a sliding hip screw. The Omega3 Trochanteric Stabilizing Plate is a relatively new device that functions like a modified sliding hip screw with a proximal extension; however, its mechanical properties have not been evaluated. This study biomechanically compared a cephalomedullary nail, that is, Gamma3 Nail against the Omega3 plate. Unstable intertrochanteric fractures were created in 24 artificial femurs. Experimental groups were as follows: Nail (i.e. Gamma3 Nail) (n = 8), Plate A (i.e. Omega3 plate with four distal non-locking screws and no proximal locking screws) (n = 8), Plate B (i.e. Plate A plus five proximal locking screws) (n = 8), Plate C (i.e. Omega3 plate with three distal locking screws and no proximal locking screws) (n = 8), and Plate D (i.e. Plate C plus five proximal locking screws) (n = 8). All specimens were stiffness tested, while the Nail and Plate D groups were also strength tested. For lateral bending, Plate B was less stiff than the Nail (p = 0.001) and Plate A (p = 0.009). For torsion, Plate A was less stiff than Plate D (p = 0.020). For axial compression, the Nail was less stiff than Plate A (p = 0.036) and Plate B (p = 0.008). Axial strength for the Nail (5014 ± 308 N) was 66% higher than the Plate D construct (2940 ± 411 N) (p < 0.001). All Nails failed by partial or complete cutout through the femoral head and neck, but Plate D failed by varus collapse and deformation of the lag screw. When the cephalomedullary nail is clinically contra-indicated, this study supports the use of the Omega3 plate, since it had similar stiffness in three test modes to the Gamma3 Nail, but had lower strength. Stability of Omega3 plate constructs was not improved with locked fixation proximally or distally.